The animal outside the text - Lestel, D.; Chrulew, Matthew (2014)
© 2014 Taylor and Francis. This interview ranges across a number of topics relevant to Dominique Lestel's thought: the history and philosophy of ethology; animal culture; realist-Cartesian and bi-constructivist ethology; biosemiotics; philo-sophical anthropology; animal studies; the other-than-human; veganism; and technology. It touches on thinkers including Bruno Latour, Jacques Derrida, Michel Foucault, Gilles Deleuze, Paul Shepard, and Donna Haraway.